HISTORY OF CHHATTISGARHI LITERATURE: AN INTRODUCTION: छत्तीसगढ़ी साहित्य का इतिहास: एक परिचय - Sahu, Yogesh (International Journal of Research -GRANTHAALAYAH, 2019)
Chhattisgarh has its own historical background, in which Chhattisgarhi literature has been confined for a hundred years. The development of Chhattisgarhi folk literature has been created by the beliefs, culture and civilizations of Chhattisgarhi folk. Literary works composed in Chhattisgarhi language had started about a thousand years ago, but there was not enough literature created at that time, yet Chhattisgarhi Literary Tours literary works composed in different times are available. "This one thousand years literary journey is divided into three classes based on different eras. 1: - 1. Saga era: from 1000 to 1500 AD 2. Bhakti era: from 1500 to 1900 AD 3. Modern era: 1900 to date छत्तीसगढ़ की अपनी ऐतिहासिक पृष्ठभूमि है, जिसमें छत्तीसगढ़ी साहित्य को सौ वर्षों तक सीमित कर दिया गया है। छत्तीसगढ़ी लोक-साहित्य का विकास छत्तीसगढ़ी लोक की मान्यताओं, संस्कृति तथा उसकी सभ्यताओं से निर्मित हुआ है। छत्तीसगढ़ी भाषा में रचित साहित्यिक रचनाओं का आरंभ लगभग एक हजार वर्ष पूर्व हो चुका था, लेकिन उस समय पर्याप्त मात्रा में साहित्य-सृजन नहीं हुआ था फिर भी छत्तीसगढ़ी साहित्यिक-यात्रा विभिन्न कालों में रचित साहित्यिक रचनाएँ उपलब्ध हैं। ‘‘इस एक हजार वर्षों के साहित्यिक यात्रा को विभिन्न युगों के आधार पर तीन वर्गों में विभाजित किया गया है1:- 1. गाथा युग: 1000 से 1500 ई. तक 2. भक्ति युग: 1500 से 1900 ई. तक 3. आधुनिक युग: सन् 1900 से आज तक